Advantages of nanofibrous membranes for culturing of primary RPE cells compared to commercial scaffolds. Issue 5 (22nd October 2021) - Tichotová, Lucie; Studenovska, Hana; Petrovski, Goran; Popelka, Štěpán; Nemesh, Yaroslav; Sedláčková, Miroslava; Drutovič, Saskia; Rohiwal, Sonali; Jendelová, Pavla; Erceg, Slaven; Brymová, Anna; Artero‐Castro, Ana; et al.
ABSTRACT: Purpose: Dysfunction of the retinal pigment epithelium (RPE) causes numerous forms of retinal degeneration. RPE replacement is a modern option to save vision. We aimed to test the results of transplanting cultured RPEs on biocompatible membranes. Methods: We cultivated porcine primary RPE cells isolated from cadaver eyes from the slaughterhouse on two types of membranes: commercial polyester scaffolds Transwell (Corning Inc., Kenneburg, ME, USA) with 0.4 µm pore size and prepared Poly (L‐lactide‐co‐DL‐lactide) (PDLLA) nanofibrous membranes with an average pore size of 0.4 µm. Results: Five types of assays were used for the analysis: immunocytochemistry (ICC), phagocytosis assay, Western blotting, real‐time qPCR (RT‐qPCR) and electron microscopy. RT‐qPCR demonstrated that RPEs cultured on nanofibrous membranes have higher expressions of BEST1 (bestrophin 1), RLBP1 (retinaldehyde‐binding protein 1), RPE65 (retinal pigment epithelium‐specific 65 kDa protein), PAX6 (transcription factor PAX6), SOX9 (transcription factor SOX9), DCT (dopachrome tautomerase) and MITF (microphthalmia‐associated transcription factor). ICC of the RPEs cultured on nanofibrous membranes showed more intensive staining of markers such as BEST1, MCT1 (monocarboxylate transporter 1), Na + /K + ATPase, RPE65 and acetylated tubulin in comparison with commercial ones. Additionally, the absence of α‐SMA proved the stability of the RPE polarization state and the absence of epithelial‐to‐mesenchymal transition. RPE possessed high phagocytic activity. Electron microscopy of both membranes confirmed a confluent layer of RPE cells and their genuine morphological structure, which was comparable to native RPEs. Conclusions: Retinal pigment epitheliums cultured on polylactide nanofibrous membranes improved the final quality of the cell product by having better maturation and long‐term survival of the RPE monolayer compared to those cultured on commercial polyester scaffolds. PDLLA‐cultured RPEs are a plausible source for the replacement of non‐functioning RPEs during cell therapy.